Nilai Perusahaan pada Industri Pertambangan dengan sudut pandang: CSR Disclosure dan Financial Distress - Anggraeni, Annisa Fitri; Lastari, Ai; Yulianti, Maria Lusiana; Rayi, Idham Ramadhan (FEB-Telkom University Publisher, 2024)
This research aims to examine the effect of CSR disclosure and financial distress on company value in the mining industry for the 2018-2022 period. This research method uses a quantitative approach with secondary data in annual reports and mining industry sustainability reports. Of the 63 mining industry companies, the sample in this study was 35 mining companies which were analyzed using panel data regression analysis assisted by eviews. The research results explain that CSR disclosure and financial distress have a simultaneous and significant effect on company value in the mining industry for the 2018-2022 period. Partially, CSR disclosure has a negative and significant effect on company value, and financial distress has a positive and significant effect on company value. This shows that the higher the CSR disclosure in the annual report, the lower the company value. Also, the higher the financial distress value using the Altman z-score ratio, the better the company value. Keyword: CSR Disclosure; Financial Distress; Firm Value